2022
DOI: 10.1002/mp.15843
|View full text |Cite
|
Sign up to set email alerts
|

A device‐agnostic shape model for automated body composition estimates from 3D optical scans

Abstract: Background: Many predictors of morbidity caused by metabolic disease are associated with body shape. 3D optical (3DO) scanning captures body shape and has been shown to accurately and precisely predict body composition variables associated with mortality risk. 3DO is safer, less expensive, and more accessible than criterion body composition assessment methods such as dual-energy X-ray absorptiometry (DXA). However, 3DO scanning has not been standardized across manufacturers for pose, mesh resolution, and post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
(40 reference statements)
1
18
0
Order By: Relevance
“…The selected features affect the classification of obesity more than the unselected features. We also compared with the model provided by Tian et al 52 . Denotes, Tian's model is a regression model, not a classification model, and we obtained results by dividing it by the criteria of the Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The selected features affect the classification of obesity more than the unselected features. We also compared with the model provided by Tian et al 52 . Denotes, Tian's model is a regression model, not a classification model, and we obtained results by dividing it by the criteria of the Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This would provide better prediction of metabolic health and identify people at high risk of disease in the long term so that remedial action can be taken. Significant works in recent years have focused on the development of 3D optical (3DO) scanning 9 to estimate body composition [10][11][12][13] . 3DO scanners use depth sensors by projecting infrared patterns onto the scan subject to rapidly construct a 3D point cloud using multiview stereo, and subsequently capture 3D surface shape information.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than predicting body composition from anthropometric measurements alone, 3D body shape as a whole provides more visual and implicit cues for predicting body composition more accurately. Additional 3D shape cues can either be additional landmark diameters, circumferences, surface areas and volumes from 3DO scans 14 , or parameters of a PCA shape space [11][12][13] . More recently, Leong et al 15 use a variational autoencoder (VAE) 16 to learn latent DXA encoding, and map 3DO scans to pseudo-DXA images.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that body shape descriptors by the 3DO mesh were more predictive of body composition as compared to DXA and were correlated to metabolic biomarkers (23). Since then, the methodology to obtain these body shape descriptors have improved by incorporating automated processing methods, agnostic models across multiple 3DO scanners, pose-independent models, and a 2D to 3D pipeline (24)(25)(26)(27). Although much has been accomplished in this field in a short amount of time, 3DO body composition has not been evaluated at the subgroup level.…”
Section: Introductionmentioning
confidence: 99%